2013
DOI: 10.1111/inr.12059
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence against nurses in emergency departments in Jordan

Abstract: Large-scale studies investigating the consequences of violence on nursing satisfaction and the quality and quantity of care administered to the community in the healthcare sector are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
86
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(114 citation statements)
references
References 29 publications
23
86
1
4
Order By: Relevance
“…The findings of our study were in coherence with many studies which indicate that nurses are exposed to high rates of workplace violence. 1,19,[26][27][28][29][30][31][32][33][34][35][36][37] These findings are a cause of concern considering the fact that workplace violence is associated with intentions to leave the profession. 22,38 The current study indicated that in majority of cases patients relatives were the perpetrators of the violence.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of our study were in coherence with many studies which indicate that nurses are exposed to high rates of workplace violence. 1,19,[26][27][28][29][30][31][32][33][34][35][36][37] These findings are a cause of concern considering the fact that workplace violence is associated with intentions to leave the profession. 22,38 The current study indicated that in majority of cases patients relatives were the perpetrators of the violence.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace violence is not confined to South Africa; for instance recent studies have shown that it occurs in Jordan (35), Pakistan (36), and China (37). Guidelines have been developed by the World Health Organization (WHO) in order to address workplace violence (38) and governments must implement strategies to ensure occupational safety.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses comprise the majority of workers in healthcare settings. Being in the front line of the healthcare system, nurses are more vulnerable to be attacked by patients, families and other co‐workers (AbuAlRub & Al‐Asmar ; Ahmed ; Albashtawy ; Ayranci ; Chen et al. ; Hesketh et al.…”
Section: Introductionmentioning
confidence: 99%
“…Jordanian nurses are not an exception; like other nurses worldwide, they commonly experience violence at their workplace (AbuAlRub & Al‐Asmar ; Ahmed ; Albashtawy ). Recent reports show that workplace violence among Jordanians is as high as 75% (Albashtawy ).…”
Section: Introductionmentioning
confidence: 99%